'Lions led by donkeys'? Britain's war in Afghanistan, 2001–2014. (December 2021) - Dixon, Paul
This article argues that Theo Farrell's book Unwinnable is a semi-official British Army history of the Afghan war and reflects the 'dominant military narrative'. The book's argument is contradictory, it suggests that NATO was 'learning, adapting and winning' the war but the politicians stabbed the military in the back by withdrawing just as a turning point had been reached in 2009-11. This was Farrell's optimistic analysis when the war was ongoing. But Unwinnable also argues that the war was unwinnable from 2001. This implies that it was the military elite that blundered because of their enthusiasm for the escalation of Britain's involvement in an unwinnable and, therefore, futile war. Unwinnable tries to rescue 'counterinsurgency' by trying to claim, implausibly, that it was only properly implement during 2009-11. Farrell champions the empowerment of the military elite and is unconcerned that the politicians struggled to exert democratic control over the military.